Interaction between Cutibacterium acnes, bacteriophages and keratinocytes as a study model of acne phage therapy (2024)
Acne is one of the most prevalent skin disorders worldwide. It is an inflammatory disease in which several factors are part of its pathogenesis: hormonal activity, hyperkeratosis, hyperseborrhea and colonization with the bacterium Cutibacterium acnes (formerly Propionibacterium acnes) (Cong et al., 2019; Kurokawa et al., 2009; Williams et al., 2012). There are six phylotypes identified for this microorganism: IA1, IA2, IB, IC, II, and III. In healthy skin, all phylotypes coexist in population equilibrium. However, in acne the population of phylotype IA1 is increased (Dagnelie et al., 2019). This phylotype stimulates cytokine production in sebocytes, keratinocytes, and neutrophils, maintaining and increasing inflammation in the skin (Barnard et al., 2016; Fitz-Gibbon et al., 2013). To treat acne, there are several drugs available, including antibiotics, which are useful due to their anti-inflammatory properties (Marson & Baldwin, 2019). Some of these drugs present side effects that compromise patient adherence to treatment. Also, it has been reported bacterial resistance for commonly used antibiotics to treat acne (Dessinioti & Dréno, 2020) making necessary to identify new alternatives to antibiotic therapy (World Health Organization, 2015). One alternative is phage therapy: using bacteriophages (phages), bacterial viruses, to control bacterial infections (Kutter et al., 2010). One of the advantages of phage therapy is its specificity since phages are generally species-specific; even some are restricted to the strain level (Hyman & Abedon, 2010). Besides, there are studies that had reported immunomodulatory properties for some bacteriophages, for instances, reducing inflammatory cytokine production (Van Belleghem et al., 2019). The principal objective of this project is to evaluate the effectivity of C. acnes bacteriophages from two perspectives: their potential to control the phylotype IA1 and its effect on the impact of C. acnes on skin cells. Host range for a collection of 10 lytic phages to isolates of different phylotypes showed that no phage is IA1-specific. However, four phages (PhiA, PhiC, Phi5, and Phi7.3) showed a diminished activity for other phylotypes. Also, plating efficiency demonstrated that these phages have differences in their efficiency to lyse phylotype IA1 isolates, being PhiA and Phi7.3 more active against IA1 isolates compared with other phylotypes. To investigate the phage’s potential to control C. acnes in skin cells a colonization model with three phylotypes (IA1, IB, and II) on Human Epidermal Keratinocytes (HEKa) co-cultures were stablished. Bacterial impact on HEKa was evaluated by cytotoxicity estimation through MTT assay, and by counting of viable cells with trypan blue. It was found that phylotypes IA1 and IB have a similar cytotoxic effect, dependent upon bacterial cell density inoculation, while phylotype II did not cause such cytotoxic effect. Inoculation with all phylotypes caused a delay in logarithmic growth phase, though the effect of phylotype IA1 on cell growth was sharper. Interestingly, phylotype II produced an increased cell proliferation. Finally, IL-1b expression was also evaluated with RT-qPCR from keratinocytes inoculated with the three different phylotypes. All bacterial isolates may increase IL-1b expression. However, only IA1 increased this cytokine expression in HEKa in a higher and more consistent manner. After the establishment of the HEKa colonization model with C. acnes IA1, it was assessed the potential of phages to ameliorate bacterial effect on keratinocytes. Phages PhiA, PhiC, Phi5, and Phi7.3 reduce C. acnes IA1 inoculum in a C. acnes-HEKa co-culture. Also, it was recorded a reduction of cytotoxicity on a different level for each phage, dependent upon concentration and purification. Purified PhiA, PhiC, and Phi7.3 were able to restore cell growth of C. acnes IA1-inoculated HEKa, which was higher for the last two phages. Alongside, inoculation of phages Phi7.3 and Phi5 reduced the IL-1b expression of colonized keratinocytes, regardless of their cytotoxicity and cell growth behavior. Overall, it is concluded that phages have a dual expected effect for acne phage therapy: the reduction of IA1 negative impact on keratinocytes and the control of this phylotype. The results here shown support the potential application of phage therapy in acne treatment, given the innocuity of phages to keratinocytes and the reduction of bacterial impact in these skin cells. Although this study explores interactions between phages, C. acnes, and skin cells, it opens the field to more detailed and comprehensive research on phage interactions with skin immunity and their influence on skin microbiota.